Low-cost tv listening device for hearing impaired persons / Faizal Mansor - Mansor, Faizal (1995)
The design of a low-cost practical wireless receiver with volume-control and transmitter for hearing impaired person to hear TV sound are presented in this thesis [1]. A trade-off design approach is introduced to solve the problem of minimizing the size of the receiver and at the same time maximize its performance. The main activity of the system is the development of appropriate technology for flexibility, durability and portability of the receiver and transmitter. It has been designed for a single supply voltage of approximately 6V for the receiver and 9V for the transmitter which reduces its power consumption. It is also designed to suit the objective function in terms of overall cost of the device. Experimental results using intergrated circuits shows that the receiver can detect each valid frequency from the transmitter within the nominal value of 700kHz.